Resusitasi Jantung Paru Dalam Kondisi Pandemi Covid -19 - Imam Suyuthi (Universitas Muhammadiyah Surabaya, 2023)
AbstractCardiopulmonary resuscitation (CPR) is a complex activity consisting of airway management, chest compressions, drug therapy and defibrillation. In airborne infections, consideration should be given to procedures that generate aerosols. During a pandemic, there needs to be a balance between the risks and benefits of performing CPR from initially no harm in trying to little benefit for the patient and significant potential harm to health care staff.Keywords : Resusitation, COVID-19, Pndemic